Genetic Diversity and Cluster Analysis of Ethiopian Hot Pepper Genotypes Using Multivariate Approaches (Indian Journal of Advanced Botany (IJAB), 2026)
Hot peppers are widely used as a spice for flavour enhancement, colouration, and seasoning, with increasing global demand. This study, conducted during the 2022/2023 cropping season, aimed to evaluate genetic variability among landrace accessions and their trait associations using multivariate analysis under semi-irrigation conditions. A total of 19 landrace genotypes and 1 improved variety were assessed across 12 quantitative and 9 qualitative traits. A randomized complete block design (RCBD) with three replications was employed. Cluster analysis categorized the genotypes into three groups: Cluster I (10 genotypes), Cluster III (6 genotypes), and Cluster II (4 genotypes). The highest genetic divergence was observed between Cluster I and Cluster II (74.20), followed by Cluster II and Cluster III (44.87) and Cluster I and Cluster III (31.86). The considerable genetic distance among these clusters suggests that they could be used in breeding programs to develop improved varieties. Principal component analysis (PCA) identified five significant principal components (PCs), with eigenvalues ranging from 2.51 to 1.44, accounting for 77.74% of the total variance. The first four PCs contributed 20.93%, 20.29%, 14.75%, and 12.02%, respectively. This study highlights the broad genetic diversity among Ethiopian hot pepper genotypes, providing valuable insights for future breeding programs and germplasm conservation.